Pretreatment with an antibiotics cocktail enhances the protective effect of probiotics by regulating SCFA metabolism and Th1/Th2/Th17 cell immune responses - Jing Xu; Haoming Xu; Xue Guo; Hailan Zhao; Jiaqi Wang; Jianhong Li; Jie He; Hongli Huang; Chen Huang; Chong Zhao; Yingfei Li; Youlian Zhou; et al. (BMC Microbiology, 2024)
Abstract Background Probiotics are a potentially effective therapy for inflammatory bowel disease (IBD); IBD is linked to impaired gut microbiota and intestinal immunity. However, the utilization of an antibiotic cocktail (Abx) prior to the probiotic intervention remains controversial. This study aims to identify the effect of Abx pretreatment from dextran sulfate sodium (DSS)-induced colitis and to evaluate whether Abx pretreatment has an enhanced effect on the protection of Clostridium butyricum Miyairi588 (CBM) from colitis. Results The inflammation, dysbiosis, and dysfunction of gut microbiota as well as T cell response were both enhanced by Abx pretreatment. Additionally, CBM significantly alleviated the DSS-induced colitis and impaired gut epithelial barrier, and Abx pretreatment could enhance these protective effects. Furthermore, CBM increased the benefit bacteria abundance and short-chain fatty acids (SCFAs) level with Abx pretreatment. CBM intervention after Abx pretreatment regulated the imbalance of cytokines and transcription factors, which corresponded to lower infiltration of Th1 and Th17 cells, and increased Th2 cells. Conclusions Abx pretreatment reinforced the function of CBM in ameliorating inflammation and barrier damage by increasing beneficial taxa, eliminating pathogens, and inducing a protective Th2 cell response. This study reveals a link between Abx pretreatment, microbiota, and immune response changes in colitis, which provides a reference for the further application of Abx pretreatment before microbiota-based intervention.